AAGBS sharing session: re-thinking assessments for postgraduates in the new normal - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2020)
The AAGBS sharing session, hosted by the Arshad Ayub Graduate Business School (UiTM), took place on 11 September 2020. The session, conducted via Cisco Webex, focused on "Re-Thinking Assessments for Postgraduates in The New Normal" featuring speaker YBhg. Professor Dr. Abd Karim Alias (Director, Centre for Development of Academic Excellence (CDAE), Universiti Sains Malaysia (USM)).